Equity Level of Health Insurance Ownership in Indonesia - Hartono, Risky Kusuma (UI Scholars Hub, 2017)
Social health insurance from government program are expected to be able to reduce inequalities access to health services in the middle of rising of health care cost, while private health insurance is still limited for up and middle class population. This study aimed to analyze the equity level of health insurance ownership including social and private health insurance in Indonesia. This study examined the condition of Indonesia in the middle of entering National Health Insurance (NHI) era. This study used data of Indonesian Socio-Economic Survey 2012. Data were analyzed by using econometric approach through multinomial logit analysis. The results showed that the concentration index of social health insurance ownership was 0.615, which is smaller than private health insurance ownership (0.972). It means that Indonesia social health insurace ownership will be able to increase equity access to the health services especially for poor people (pro poor). Social health insurance ownership increases the use of the health services by people.